PERAN ORANG TUA TERHADAP PERILAKU ANAK REMAJA MENGONSUMSI TUAK DI DESA BAKAL JULU KABUPATEN DAIRI SUMATERA UTARA - Sijabat, Pilipus; Zuryani, Nazrina; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 2 No 01 (2022): JISSOROT, 2022)
Nowadays, adolecents are lacking of self-control and act on their own pathways without considering other people around them. Many youngsters in my village, Bakal Julu drink Tuak (popular traditional alcoholic drink) at kode (house cafe/warung) during day time and even night. Some of these youngsters are mostly schoolers. Oftentimes, parents ignore them as if they seem not care and let them do it repeatedly by saying too tired of reminding them not to but they keep on drinking it purposely. This research is aimed to describe and clearly explain the factors of why these youngsters drink tuak and parents' role in preventing them to not drink it. This research is conducted using qualitative method with descriptive explanatory way of design. This reasearch was supported by a popular American sociologist Travis Hirschi on his theory "Social Control". The results of this research has obviously shown that the causes of these youngsters drink tuak are environment, the impact of negative friendship, lacking of strict parenthal controls and lacking of strict rules to not drink tuak as well. Bad relationship between both child and their parents has also led children to not understand what family is and its functions and in fact they choose friends over family. Parents whose habits are drinking tuak has also faded youngsters' belief that tuak is a drink that contains of addictive substances that can cause addiction. Key words: The Role of Parents, Teenagers, Tuak